Social Character Education in the Perspective of the Qur'an and Hadith - Nurhidaya M; Basir, Abd; Barni, Mahyuddin; Khaeruddin, Ahmad (Al Qalam, 2023)
This research discusses the meaning of social education and its value ​​in forming social character from the perspective of the Qur’an and Hadith. The assessment was done through a literature review, taking references from commentaries, books, journals, and related articles, accessed online via the Internet network. There are many values ​​of social character education taught in the Qur'an and Hadith, such as brotherhood, mutual help, caring, forgiveness, tolerance, mutual giving, not being individualistic, and giving each other space to others. Many more social and community education values ​​are presented in the Al-Qur'an and Hadith, which can be used to form social character. Due to limitations, several examples of social and social education values are taken, ​​as informed in the Al-Qur'an and Hadith.